Kontribusi Usaha Tambak Garam Rakyat Terhadap Pendapatan Rumah Tangga Petani Di Kabupaten Lombok Timur - Syahrin, Muhammad Alfi; Husni, Syarif; Amiruddin, Amiruddin (Universitas Mataram, 2025)
This study aims to: 1) analyze the costs and income of people's salt businesses in East Lombok Regency. 2) analyze the income of farmer households outside the people's salt business in East Lombok Regency. 3) determine the contribution of people's salt businesses to the income of farmer households in East Lombok Regency. 4) determine the obstacles faced by people's salt businesses in East Lombok Regency. The method used in this study is a descriptive method. The number of respondents was determined as many as 32 farmer households (RTP) by Quota sampling. From this number, using the Proportional Random Sampling method, 28 RTPs in Pemongkong Village and 4 RTPs in Ketapang Raya Village, East Lombok Regency were selected. The results of the study showed that; 1) People's salt businesses in East Lombok Regency spend production costs of Rp. 12,970,016 per year with a total income of Rp. 92,903,125 per year, so that the income of the people's salt business obtained is Rp. 79,933,109 per year per LLG (0.5 Ha). 2) Income outside the community salt business per year in farmer households, namely rice farming income of Rp. 1,032,115, corn farming of Rp. 6,169,344, milkfish pond business of Rp. 292,500, and income from other sources of Rp. 9,216,250 with a total income of Rp. 16,710,209 per year. 3) The contribution of the community salt business to the income of farmer households is worth Rp. 79,933,109 per year from the total income of farmer households of Rp. 96,643,318 per year with a contribution percentage of 78.25% per year. 4) Constraints in the community salt business faced by community salt farmers are unstable selling prices, unpredictable weather, sea water quality, and technology that has not been utilized in the salt production process